Edukasi dan Pemeriksaan Kesehatan Gigi Anak Usia Dini di Dusun Gayasan Kecamatan Jenggawah Kabupaten Jember - Amara Kanya Maharan; Tsabitah Salsabil Aqilah; Syafiya Zata Yumni; Liesna Lusyana Nur; Banun Kusumawardani (Dental Agromedis, 2023)
Early childhood is a vulnerable group for dental and oral health. Children at an early age are in the process of growth and development, and need attention and assistance from their parents in maintaining healthy teeth. The PKM-PM UNEJ aims to 1) increase knowledge about maintaining dental health for parents and early childhood; and 2) conduct dental health check-ups for early childhood. Implementation of activities is carried out by providing modules, practices, and questionnaires to measure target knowledge. The main potential of early childhood dental education and examination in Gayasan Hamlet, Jenggawah Village, Jember Regency is that early childhood can understand proper and correct tooth brushing techniques and methods accompanied by their parents. Partners are very enthusiastic and support PKM-PM activities. Next, partners really hope to be able to realize family dental health by preventing caries from an early age to support children's growth and development.Keywords: early childhood, developmental disorders, dental health